Radiotherapy and Nuclear Medicine Equipment Shortages in Vietnam: A Critical Gap in Cancer Care - Dang Van Nguyen; Manh Duy Pham; Thai Huu Hoang; Binh Thanh Nguyen (JCO Global Oncology)
PURPOSEThe aim of this study was to evaluate the current availability and distribution of radiotherapy (RT) and nuclear medicine equipment in Vietnam, focusing on the shortage of linear accelerators (LINACs), positron emission tomography/computed tomography (PET/CT) scanners, and brachytherapy units. The study seeks to quantify these shortages and highlight the implications for cancer treatment access and outcomes.METHODSData were collected from 50 hospitals across Vietnam that provide RT services or nuclear medicine imaging. The availability of LINACs, PET/CT devices, brachytherapy units, and other essential equipment was assessed, alongside patient loads and machine utilization rates. National data were compared with the standard in developed countries, with a particular focus on the International Atomic Energy Agency's (IAEA) recommendations for RT infrastructure.RESULTSVietnam has a total of 82 LINACs, resulting in a LINAC density of 0.82 per million people, which is far below the standard in developed countries of 4-8 per million. Of the existing LINACs, 43% are outdated and unable to deliver advanced RT techniques such as volumetric modulated arc therapy. Additionally, the country has only 12 PET/CT scanners and three cyclotrons, which limits access to early cancer diagnosis and treatment planning. The central region of Vietnam is particularly underserved, with only 1 PET/CT device and limited access to brachytherapy services. Long wait times for RT—often up to 2 weeks—are common, leading to delayed treatments and reduced treatment efficacy. Patients, particularly those with conditions requiring timely RT after chemotherapy, face increased risks because of these delays.CONCLUSIONThe shortage of modern RT and nuclear medicine equipment in Vietnam critically limits timely access to cancer treatment, affecting patient outcomes and placing a heavy burden on health care providers. Expanding access to advanced RT technology through government investment, public-private partnerships, and international collaborations with organizations such as the IAEA could alleviate these challenges. Increasing Vietnam's RT capacity is essential for improving cancer care outcomes and managing the rising burden of cancer across the country.